2010
DOI: 10.1080/10400419.2010.481513
|View full text |Cite
|
Sign up to set email alerts
|

Intuition as an Influence on Creative Problem-Solving: The Effects of Intuition, Positive Affect, and Training

Abstract: Intuition may be a critical component of creative thought. To test this hypothesis, a measure of individual differences in intuition was developed. After completing this measure, 320undergraduates were asked to work on a domain relevant creative problem-solving task under conditions where positive and neutral affect were induced and they were exposed to one of three different types of training. It was found that intuitive people produced more creative problem solutions, but that positive affect and training of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 60 publications
0
25
0
1
Order By: Relevance
“…Isen's studies have consistently shown that positive mood inductions lead to better, more efficient decision making, including decision making requiring more careful, systematic, and thorough processing. Several recent studies continue to show beneficial effects of positive affect (Eubanks, Murphy, & Mumford, 2010;Xiao, Wang, Chen, Zheng, & Chen, 2015).…”
mentioning
confidence: 99%
“…Isen's studies have consistently shown that positive mood inductions lead to better, more efficient decision making, including decision making requiring more careful, systematic, and thorough processing. Several recent studies continue to show beneficial effects of positive affect (Eubanks, Murphy, & Mumford, 2010;Xiao, Wang, Chen, Zheng, & Chen, 2015).…”
mentioning
confidence: 99%
“…Meanwhile, intuition has also been identified to be important in idea generation of creative professionals, such as Nobel laureates (Marton, Fensham, & Chaiklin, 1994) and Michelin chefs (Stierand & Dörfler, 2016). Moreover, this beneficial role of intuition has been supported by empirical evidence, which demonstrates that intuitive individuals are able to generate solutions of higher quality and elegance (Eubanks, Murphy, & Mumford, 2010) and of higher originality (Garfield, Taylor, Dennis, & Satzinger, 2001) to specific problems than deliberative people.…”
Section: Introductionmentioning
confidence: 76%
“…For instance, Einstein emphasized that intuition was a precious gift of human beings. Eubanks, Murphy, and Mumford (2010) concluded that intuition contributes to creative problem solving. With regard to the essence of intuition, Bastick (1982) viewed intuition as a kind of foresight ability.…”
mentioning
confidence: 98%
“…Although the source of creativity might be a multidimensional construct (Kurtzberg, 2005); creative form-production might result from visual reasoning (Goldschmidt, 1991) and creative thought might be associated with experience or intuition and triggered by training or positive affect (Eubanks et al, 2010), creativity itself might not be easily found through reasoning nor simply traced.…”
mentioning
confidence: 99%